Palmitic Acid Methyl Ester Induces G2/M Arrest in Human Bone Marrow-Derived Mesenchymal Stem Cells via the p53/p21 Pathway - Jian-Hong Lin; Pei-Ching Ting; Wen-Sen Lee; Hung-Wen Chiu; Chun-An Chien; Chin-Hung Liu; Li-Yi Sun; Kun-Ta Yang (Stem Cells International)
Bone marrow-derived mesenchymal cells (BM-MSCs) are able to differentiate into adipocytes, which can secrete adipokines to affect BM-MSC proliferation and differentiation. Recent evidences indicated that adipocytes can secrete fatty acid metabolites, such as palmitic acid methyl ester (PAME), which is able to cause vasorelaxation and exerts anti-inflammatory effects. However, effects of PAME on BM-MSC proliferation remain unclear. The aim of this study was to investigate the effect of PAME on human BM-MSC (hBM-MSC) proliferation and its underlying molecular mechanisms. hBM-MSCs were treated with PAME for 48 h and then subjected to various analyses. The results from the present study show that PAME significantly reduced the levels of G2/M phase regulatory proteins, cyclin-dependent kinase 1 (Cdk1), and cyclin B1 and inhibited proliferation in hBM-MSCs. Moreover, the level of Mdm2 protein decreased, while the levels of p21 and p53 protein increased in the PAME-treated hBM-MSCs. However, PAME treatment did not significantly affect apoptosis/necrosis, ROS generation, and the level of Cdc25C protein. PAME also induced intracellular acidosis and increased intracellular Ca2+ levels. Cotreatment with PAME and Na+/H+ exchanger inhibitors together further reduced the intracellular pH but did not affect the PAME-induced decreases of cell proliferation and increases of the cell population at the G2/M phase. Cotreatment with PAME and a calcium chelator together inhibited the PAME-increased intracellular Ca2+ levels but did not affect the PAME-induced cell proliferation inhibition and G2/M cell cycle arrest. Moreover, the half-life of p53 protein was prolonged in the PAME-treated hBM-MSCs. Taken together, these results suggest that PAME induced p53 stabilization, which in turn increased the levels of p53/p21 proteins and decreased the levels of Cdk1/cyclin B1 proteins, thereby preventing the activation of Cdk1, and eventually caused cell cycle arrest at the G2/M phase. The findings from the present study might help get insight into the physiological roles of PAME in regulating hBM-MSC proliferation.